2004
DOI: 10.2739/kurumemedj.51.35
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Difference in Epithelial and Mucosal Barrier Functions between the Jejunum and the Ileum in Cold Storage Small Bowel Grafts in the Rat

Abstract: The purpose of this study was to determine the differences in epithelial and mucosal barrier function between the jejunum and the ileum at transplantation. Rat small bowel was preserved in cold University of Wisconsin solution for 0, 12 or 24 hrs. Time-related segmental differences in the potential differences, at rest (rPD) and upon glucose stimulation (PDgs), and in the permeation rates of phenolsulfonphtalein (PSP) and polyethylene glycol 4000 (PEG) as non-absorbable markers were studied after a 20-min reox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Consistent with the present findings, a previous study has demonstrated that the ileum was more resistant to cold preservation than the jejunum (12). In contrast, the rat small intestine has exhibited no marked segmen tal difference in mucosal damage while in the Ussing chamber (5).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the present findings, a previous study has demonstrated that the ileum was more resistant to cold preservation than the jejunum (12). In contrast, the rat small intestine has exhibited no marked segmen tal difference in mucosal damage while in the Ussing chamber (5).…”
Section: Discussionsupporting
confidence: 92%
“…Previous researches reported that time-related damage of epithelial function occurred faster in the jejunum than in the ileum [ 35 ] and in a pig small transplantation experiment, which used cold ischemic and periods ranging from 0 to 12 h, estimated (based on the light microscopy) that the ileum is more resistant to preservation injury than jejunum [ 36 ]. Ulcerative colitis (UC) and Crohn's disease (CD) causes inflammation mostly in the ileum, colon, or both [ 37 ].…”
Section: Discussionmentioning
confidence: 99%